Patterns of antithyroid drug use in hyperthyroid patients at the outpatient pharmacy of hospital x from January to December 2023 - Rif'aa Naflah Faadiyah; Sylvi Adiana; Anna Uswatun Hasanah Rochjana (PT WIM Solusi Prima, 2026)
Hyperthyroidism is a condition characterized by increased production and secretion of thyroid hormones by the thyroid gland. This condition is indicated by a significant increase in triiodothyronine (T3) and thyroxine (T4) levels, which is generally caused by an autoimmune response that attacks the thyroid gland. This study aims to determine the pattern of use of hyperthyroid drugs based on medical record data and outpatient BPJS prescriptions at Hospital X during the period January to December 2023. This research is an observational study with a quantitative approach using descriptive methods, and data collection is done retrospectively. Results based on patient characteristics based on age, dominated by the age group with a range of 26-35 years as many as 56 people (29.47%) and gender dominated by women as many as 148 people (77.89%). Results based on the pattern of use of antithyroid drugs in hyperthyroid patients show that based on the type of drug, propylthiouracil (PTU) is more widely used in patients with hyperthyroidism as much as 124 uses (65.26%) and the class of drugs used in hyperthyroid patients with Thionamide group, obtained a percentage of 100%.